Cyber Counseling (2014-2023): A Bibliometric Study - Gusteti, Meria Ultra; Neviyarni, Neviyarni (Postgraduate School, Universitas Negeri Padang, 2023)
The use of cyber counseling currently plays a significant part in the execution of education. This study intends to locate and evaluate cyber counseling publications that have appeared in reputable national and international journals between 2014 and 2023. This study employs a bibliometric methodology with four stages of systematic mapping: 1) finding articles using the Publish or Perish application in the Scopus and Google Scholar databases; 2) classifying articles for bibliometric analysis; 3) ensuring that article metadata is accurate and complete and 4) bibliometric analysis using the VOSviewer application. The results of the bibliometric analysis show four main findings, namely: 1) the trend of publications about cyber counseling continues to increase from 2014 to 2023, especially during the COVID-19 pandemic; 2) the ten most cited articles get a high number of citations; 3) the three author keywords most often used in articles about cyber counseling are COVID-19, counseling, cyber counseling service and development; and 4) author collaboration with strong connectedness only occurs between several authors through one document. Overall, the research results show that cyber counseling is a popular model among researchers.